Innovative approaches to water resource management in achieving sustainable development goals - Takhumova Oksana; Goncharova Maria (E3S Web of Conferences)
Effective water resource management is pivotal in achieving the United Nations Sustainable Development Goals (SDGs), particularly Goal 6, which aims to ensure availability and sustainable management of water and sanitation for all. This paper explores innovative approaches to water resource management that contribute to the realization of SDGs. The study employs a comprehensive bibliographic analysis of recent literature, highlighting technological advancements, policy frameworks, and community-based initiatives that enhance water sustainability. Key innovations discussed include smart water technologies, integrated water resources management (IWRM), nature-based solutions, and participatory governance models. By examining case studies from diverse geographic regions, the research illustrates how these approaches address challenges such as water scarcity, pollution, and inefficient usage. The findings underscore the importance of interdisciplinary strategies that combine technological innovation with robust policy support and active community engagement. Additionally, the paper identifies barriers to the implementation of innovative water management practices, including financial constraints, lack of infrastructure, and socio-political challenges. Recommendations are provided to policymakers, practitioners, and researchers to foster the adoption of sustainable water management solutions. This study contributes to the ongoing discourse on sustainable development by offering insights into effective water management practices that align with global sustainability objectives.